Identification and Quantification of Andrographolide from Andrographis paniculata (Burm. f.) Wall. ex Nees by RP-HPLC Method and Standardization of its Market Preparations - Sajeeb, BK; Kumar, Uttom; Halder, Shimul; Bachar, Sitesh C (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Andrographis paniculata (Burm. f.) Wall. ex Nees, commonly known as Kalmegh, is widely used as antimalarial drug in herbal and traditional systems. Andrographolide is the major triterpenoid present in the plant and responsible for its therapeutic activities. The identification and quantification of andrographolide were ascertained by various spectrophotometric and chromatographic analyses. The plant sample was extracted with methanol. The amorphous residue obtained from extraction was analyzed for identification of andrographolide by chemical method, TLC, UV-Vis, FT-IR and LCMS/MS analyses. The quantitative estimation of andrographolide content in plant sample was carried out by simple reversed phase HPLC method with C18 column using a mixture of water and methanol (35:65) as mobile phase at a flow rate of 0.7 mL/min, and the estimated concentration level of andrographolide was found as 38.36±0.42 ?g/mL in the solution of amorphous residue (50 ?g/mL). After quantitative determination of andrographolide, standardization of its market preparations was accomplished using the same RP-HPLC method. The estimated % potencies of andrographolide compared to reference standard in six market preparations were found to be 97.56, 98.37, 98.21, 95.60, 98.91 and 96.40. Dhaka Univ. J. Pharm. Sci. 14(1): 71-78, 2015 (June)